Analyzing Predictors of Bullying Victimization With Routine Activity and Social Bond Perspectives. Issue 18 (September 2019) - Cecen-Celik, Hatice; Keith, Shelley
Bullying victimization in school settings is a serious problem in many countries including the United States. It has been associated with serious incidents of school violence as well as detrimental physical, psychological, emotional, and social consequences for its victims. Given its consequences, it is crucial to understand who is more likely to be targeted for bullying victimization. This study examines whether a number of important factors such as gender, physical and interactionist school security measures, and involvement in extracurricular activities influence an individual's risk of bullying victimization from social bond and routine activity perspectives. The study employs the 2011 School Crime Supplement of the National Crime Victimization Survey to investigate the causes of bullying victimization. The results show that gender, interactionist school security measures, and extracurricular activities affect an individual's likelihood of bullying victimization.